2010
DOI: 10.1371/journal.pone.0012379
|View full text |Cite
|
Sign up to set email alerts
|

Care Seeking Behavior of Chest Symptomatics: A Community Based Study Done in South India after the Implementation of the RNTCP

Abstract: IntroductionWith the creation of the Revised National TB Control Programme (RNTCP), tuberculosis services have become decentralized and more accessible. A 1997 study prior to RNTCP implementation reported that most chest symptomatics accessed first private health care facilities and a general dissatisfaction with government health facilities. The study was repeated post-RNTCP implementation to gain insight into the current care seeking behavior of chest symptomatics.MethodologyA cross-sectional community-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 1 publication
5
70
3
Order By: Relevance
“…The symptoms suggestive of PTB and various types of HCPs reported in the included studies are summarized in Table 1. Nine studies 17, 20, 21, 23, 25, 29, 31-33 used onset of symptoms as any of the five cardinal TB manifestations i.e. cough ≥ 3 wks with/without chest pain, with or without fever, with or without loss of weight, with or without haemoptysis.…”
Section: Resultsmentioning
confidence: 99%
“…The symptoms suggestive of PTB and various types of HCPs reported in the included studies are summarized in Table 1. Nine studies 17, 20, 21, 23, 25, 29, 31-33 used onset of symptoms as any of the five cardinal TB manifestations i.e. cough ≥ 3 wks with/without chest pain, with or without fever, with or without loss of weight, with or without haemoptysis.…”
Section: Resultsmentioning
confidence: 99%
“…We controlled for treatment delays in two ways [43-51]. First, we used the number of weeks between symptom onset and treatment initiation.…”
Section: Methodsmentioning
confidence: 99%
“…4 A study from Tamil Nadu, South India reported that 38% of chest symptomatic patients first approached private health facility for their diagnosis and treatment. 6 Similarly, a community-based survey from 30 districts of India reported that nearly half of TB patients (46%) were treated under Non-RNTCP sources, among them, 21% were re-treatment TB cases. 4 In the present study, the male to female (M: F) ratio of retreatment TB patients was approximately 6:1.…”
Section: Discussionmentioning
confidence: 99%